Quest for high-performance gel polymer electrolyte by enhancing the miscibility of the bi-polymer blend for lithium-ion batteries: performance evaluation in extreme temperatures. (April 2023) - Balakrishnan, N.T.M.; Das, A.; Joyner, J.D.; Jabeen Fatima, M.J.; Raphael, L.R.; Pullanchiyodan, A.; Raghavan, P.
Abstract: A novel approach to enhance the miscibility of polyvinylidene difluoride (PVdF)/polymethyl methacrylate (PMMA) blend polymer electrolyte is introduced by in - situ polymerization of methyl methacrylate monomers in PVdF matrix. The phase inversion membrane of PVdF/PMMA blend exhibits uniform microporous structure with high porosity, better electrolyte uptake (413%), retention, and lower contact angle. The structural characterization of the membranes is analyzed with Fourier transform infrared spectroscopy. The thermal stability is examined by thermogravimetric analysis and differential scanning calorimetry. The miscibility of the blend is confirmed from examining the blend solution for 100 days. The optimized blend electrolyte system with 50 wt% of the PMMA (gel polymer electrolyte [GPE-50]) reveals better ionic conductivity of 5.2 mS/cm at room temperature. The GPE is capable to establish high anodic stability up to 4.8 V vs. Li/Li + and a better electrode compatibility. The initial discharge capacity observed for the Li/LiFePO4 cell with GPE-50 is about 162 mAh/g at 0.1C at 25 °C with 95% of cathode utilization of the material. The device-level evaluation ensures that the GPE with good charge–discharge performance and stable cycling can be used for future lithium-ion batteries. Highlights: In-situ blend of polyvinylidene difluoride/polymethyl methacrylate blend is fabricated as the novel polymer electrolyte for lithium-ion battery. The in-situ blending improves the miscibility of the bipolymer blend compared to the physical blend. Phase inversion method is adopted to fabricate porous polymer membrane. The in-situ blend electrolyte outperforms in rechargeable lithium-ion batteries even at extreme temperature range.